Algunos fundamentos filosóficos y psicológicos de la tecnología educativa - Verdecia Carballo, Enrique (Edutec, Revista Electrónica de Tecnología Educativa, 2007)
El presente trabajo tiene como objetivo describir el surgimiento de la tecnología educativa como tendencia pedagógica contemporánea y sus referentes filosóficos y psicológicos. En especial se hace énfasis en el impacto que ha producido la tecnología educativa sobre la educación cubana y desde que presupuestos filosóficos y psicológicos se ha asumido, sin dejar de tener en cuenta sus antecedentes históricos. Abstract The technological development of the 1950s finally generated a whole educational revolution at world-wide level whose leading exponent is what today is known as distance learning. This paper aims at finding a way of describing the emergence of educational technology as a contemporary pedagogical tendency. It also describes its philosophical and pedagogical referents, since they have led the way to its present developments, even in distance learning. Our point of departure is the concept of skill (técnica) and its subsequent link with science, thus giving origin to the concept of technology, to later describe the way in which the latter gradually related to different cultural and social systems. Special emphasis is laid on the impact that educational technology has had on Cuban education and on the identification of the philosophical and psychological assumptions that have been its point of departure, taking into account its historical background.